Role of the kidneys in the metabolism of plasma mevalonate. Studies in humans and in rhesus monkeys. - McNamara, D J (1985)
Studies were carried out in humans and in rhesus monkeys to determine the role of the kidneys in the metabolism of circulating mevalonic acid (MVA). Following intravenous infusion of [14C]MVA and [3H]cholesterol, there was a rapid appearance of [14C]squalene in the kidneys that exhibited a significantly longer half-life than plasma or hepatic squalene. In man and in rhesus monkeys there was a rapid equilibration between newly synthesized cholesterol from MVA and exogenously administered cholesterol in all tissues except the kidneys, where the specific activity ratio of newly synthesized to exogenous cholesterol was significantly higher. Estimates of the quantitative metabolism of intravenously infused radiolabeled MVA in the monkey demonstrated that 23% was excreted in the urine, 67% metabolized to cholesterol (58% in nonrenal tissues and 9% in the kidneys), and 10% catabolized to CO2 and nonsteroid products. Measurements of MVA metabolism in anephric and uninephric patients demonstrate that, in the absence of renal uptake of MVA, exogenous and newly synthesized cholesterol achieve almost instantaneous equilibrium in the plasma; whereas in control subjects with normal renal function, this equilibration required at least 21 d for the two cholesterol decay curves to become parallel. These results suggest that the kidneys are solely responsible for the observed disequilibrium between newly synthesized and exogenous cholesterol; we suggest that this was due to the delayed release of newly synthesized cholesterol from the kidneys into the plasma compartment following intravenous infusion with radiolabeled MVA. The data document the importance of the kidneys in the metabolism of circulating MVA. However, calculation of the quantitative significance of this pathway in relation to whole body MVA metabolism indicates that renal metabolism of MVA accounts for approximately 0.1% of daily MVA turnover, and that alterations in this pathway due to any form of renal pathology would not result in significant changes in hepatic or whole body sterol synthesis rates. We urge caution in the use of radiolabeled MVA in long-term kinetic studies of sterol metabolism because our data show that the plasma compartment of MVA is not necessarily in isotopic equilibrium with tissue MVA.